Efficacy of Thymosin Alpha 1 in the Treatment of COVID-19: A Multicenter Cohort Study - Liu, Jiao; Shen, Yanfei; Wen, Zhenliang; Xu, Qianghong; Wu, Zhixiong; Feng, Huibin; Li, Zhongyi; Dong, Xuan; Huang, Sisi; Guo, Jun; Zhang, Lidi; Chen, Yizhu; et al. (Frontiers in Immunology, 2021)
Background: Thymosin alpha 1 (Tα1) is widely used to treat patients with COVID-19 in China, however, its efficacy remains unclear. This study aimed to explore the efficacy of Tα1 as a COVID-19 therapy. Methods: We performed a multicentre cohort study in five tertiary hospitals in the Hubei province of China between December 2019 and March 2020. The patient non-recovery rate was used as the primary outcome. Results: All crude outcomes, including non-recovery rate (65/306 vs. 290/1976, p = 0.003), in-hospital mortality rate (62/306 vs. 271/1976, p = 0.003), intubation rate (31/306 vs. 106/1976, p = 0.001), acute respiratory distress syndrome (ARDS) incidence (104/306 vs. 499/1976, p = 0.001), acute kidney injury (AKI) incidence (26/306 vs. 66/1976, p < 0.001), and length of intensive care unit (ICU) stay (14.9 ± 12.7 vs. 8.7 ± 8.2 days, p < 0.001), were significantly higher in the Tα1 treatment group. After adjusting for confounding factors, Tα1 use was found to be significantly associated with a higher non-recovery rate than non-Tα1 use (OR 1.5, 95% CI 1.1 – 2.1, p = 0.028). An increased risk of non-recovery rate associated with Tα1 use was observed in the patient subgroups with maximum sequential organ failure assessment (SOFA) scores ≥ 2 (OR 2.0, 95%CI 1.4 – 2.9, p = 0.024), a record of ICU admission (OR 5.4, 95%CI 2.1 – 14.0, p < 0.001), and lower PaO2/FiO2 values (OR 1.9, 95%CI 1.1 – 3.4, p = 0.046). Furthermore, later initiation of Tα1 use was associated with a higher non-recovery rate. Conclusion: Tα1 use in COVID-19 patients was associated with an increased non-recovery rate, especially in those with greater disease severity.